DESAFIOS DA REFORMA AGRÁRIA NO CONTEXTO DO DESENVOLVIMENTO DEPENDENTE NO ESTADO DO MARANHÃO - Francisco Elias de Araújo (Universidade Federal do Maranhão, 2018)
This text deals with agrarian development, starting from the reality of the Microregion of Chapadinha in Maranhão state. The focus is the expanse of the monoculture of soya, while capital expression, over the territory occupied by peasents, and the participation of Agrarian Reform nacional politic in the facing of fundiary questions, local development and fortification of the peasent and agroecological agriculture.